MEMBANGUN ETIKA DIGITAL REMAJA MELALUI FILSAFAT PENDIDIKAN IBNU TUFAIL - Muhammad Taufiq (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
The phenomenon of digital ethical degradation among adolescents is a pressing issue in contemporary education. Teenagers are often trapped in unethical online behaviors such as hate speech, hoaxes, and cyberbullying due to the lack of moral guidance relevant to digital realities. This article offers a philosophical approach by using the educational philosophy of Ibn Tufail especially through the allegory of Hayy bin Yaqzan as a conceptual framework for building adolescents' digital ethics. This study adopts a qualitative-descriptive approach using library research on Hayy bin Yaqzan and relevant literature on digital ethics education and youth character development. Findings reveal that Hayy's developmental stages from empirical observation to spiritual awareness align with the needs of digital ethics education that emphasizes reflection, autonomous thinking, and moral responsibility. The practical implication is the need for a digital ethics learning model based on philosophical reflection, such as digital moral dilemma discussions and media literacy projects that integrate wisdom-based values. This approach is highly relevant in addressing the character formation challenges of adolescents within a rapidly evolving technological ecosystem. Thus, Ibn Tufail's philosophical legacy proves not only historically valuable but also contextually applicable to contemporary educational needs.